PROTECTING PALESTINIAN CHILDREN IN GAZA: LEGAL ENFORCEMENT OF THE UNITED NATIONS CHILD RIGHTS CONVENTION - Gunawan, Yordan; Putra, Muhammad Raqi Pratama; Mareto, Irvan (Masalah-Masalah Hukum, 2025)
This study aims to analyze the effectiveness of the United Nations Convention on the Rights of the Child (UNCRC) in protecting children’s rights in Palestine, particularly in Gaza, which has experienced severe violations of children’s rights due to Israeli attacks since October 2023. Israel, as a state party to the UNCRC, has been found to fail in fulfilling its obligations to protect Palestinian children. The ongoing conflict has resulted in over 17,000 child fatalities, with thousands more injured and separated from their families, while their rights to life, development, education, and protection from violence have been severely breached. Although the UNCRC aims to safeguard children’s rights globally, the violations in Gaza highlight the weaknesses in its implementation. This research employs a normative legal research methodology, analyzing international legal documents, including the UNCRC, the 1948 Genocide Convention, and related international law. The findings of this study reveal that, despite Israel’s ratification of the UNCRC, the country continues to violate Palestinian children’s rights, particularly through mass killings, the destruction of educational and healthcare infrastructure, and the blockade obstructing access to essential services. This study suggests the need for strengthening international law enforcement mechanisms, including reforms in the UNCRC’s monitoring body and greater involvement of international organizations such as UNICEF, along with the removal of veto power in the UN Security Council, to ensure Israel's accountability for the violations of children’s rights occurring in Gaza.